(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article examines the issues of increasing the efficiency of the process of teaching a foreign language; it is concluded that it is necessary to optimize and improve not only the learning process, but also the forms of monitoring the results of educational activities of senior schoolchildren in the acquisition of a foreign language.